Electronic Poster Abstracts 2021
DOI: 10.1136/neurintsurg-2021-snis.241
|View full text |Cite
|
Sign up to set email alerts
|

E-146 The value of long-term angiographic follow-up following pipeline embolization of intracranial aneurysms

Abstract: Fisher exact test and in multivariate analysis using multiple logistic regression with bidirectional elimination based on the Akaike information criterion. In both univariate and multivariate analyses, statistical significance was corrected for multiple comparisons using the Benjamini-Hochberg method with a prespecified false discovery rate of 0.05. Results Complications occurred in 6.5% of procedures, including 1.9% neurological complications and 4.8% non-neurological complications. Permanent deficits occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In addition, ISS in most patients remain stable or even improved. These findings are consistent with previous studies (8)(9)(10)(11)(12)(13)(14). Reversible stenosis may be associated with thrombosis (25).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, ISS in most patients remain stable or even improved. These findings are consistent with previous studies (8)(9)(10)(11)(12)(13)(14). Reversible stenosis may be associated with thrombosis (25).…”
Section: Discussionsupporting
confidence: 94%
“…However, longterm complications of PED placement are not well understood. Previous studies have reported that most patients with ISS are asymptomatic and that ISS usually gradually improves; however, it may worsen (8)(9)(10)(11)(12)(13)(14). In addition, ISS may result in hemiplegia (14, 15) or even death (11) and cause decreased blood flow velocity (16).…”
Section: Introductionmentioning
confidence: 99%